AKSI PROTES MASYARAKAT PATI MENURUNKAN BUPATI DALAM BINGKAI PEMBERITAAN KOMPAS.COM - Irdan Hildansyah; Rusdan Kamil (Jurnal Komunikasi dan Kajian Media, 2026)
This study employs a qualitative approach using the framing analysis model developed by Zhongdang Pan and Gerald M. Kosicki. The model consists of four framing devices: syntactic, script, thematic, and rhetorical structures, which are used to examine how media construct reality through news organization, sentence structure, language use, and lexical choices. The object of this research is news coverage published by Kompas.com regarding public protests in Pati demanding the removal of the Regent. The findings reveal that law enforcement officials were the most dominant sources, appearing in 15 articles or 54% of the total news analyzed. Government sources were cited in 7 articles (25%), while protesters’ voices appeared in only 4 articles (14%). Civilian victims were the least represented, appearing in just 2 articles (7%). This imbalance indicates that the news narratives were primarily constructed from the perspective of official authorities rather than from protesters or affected citizens. Based on these findings, the study concludes that Kompas.com predominantly framed the Pati protests through a security and state stability perspective. Keywords: Framing analysis, Pati Regency, Regent, Kompas.com.